Synergistic Effect of Irregular Shaped Particles and Graphene on the Thermal Conductivity of Epoxy Composites. (5th August 2018) - Liu, Changqing; Chen, Cheng; Wang, Hongmei; Chen, Mao; Zhou, Dongyi; Xu, Zhengxia; Yu, Wei
Abstract : Improving the heat transfer properties of the thermal interface materials (TIMs) is the basic way to solve heat dissipation problem of electronic products with high energy density. In this study, the synergistic heat transfer between graphene and irregular particles at low loading is systematically studied; these irregular shaped particles include Ag, Cu, and MgO. When the mass fraction of the irregular shaped particles is <20%, the heat transfer network chain is mainly formed by the fully dispersed graphene. However, when the irregular shaped particle mass fraction reaches 30%, more heat transfer network chain will form between particles. In addition, the interfacial thermal resistance between fillers and matrix is the most crucial factor, and the intrinsic thermal conductivity of irregular particles is a relatively minor factor for the synergistic heat transfer between graphene and irregular particles at low loading. POLYM. COMPOS., 40:E1294–E1300, 2019. © 2018 Society of Plastics Engineers